ナンキョク カンソク ヨウ セツジョウシャ KD60 ノ キホン セッケイ ニツイテ - 宇宿, 行久; ウスク, ユキヒサ; 細谷, 昌之; ホソヤ, マサユキ; USUKU, Yukihisa; HOSOYA, Masayuki (国立極地研究所, 1965)
P(論文) 本南極観測用雪上車は,南極内陸調査旅行に使用する目的で設計されたものであり,短期間に試作を完了する必要があるため,現在陸上自衛隊に装備されている61式大型雪上車を母体とし,これに必要な改修を加えたものである.全備重量約8.5t,接地圧0.20kg/cm^2,乗員数3名,車体はキャブオーバー型で,車室内に暖房装置,換気装置,寝台,炊事用具等をそなえ,また,観測に必要な機器を塔載できるようになっている.エンジンは標準状態で140PSで,3台のそり約8tをけん引する場合の常用速度は約5km/hである.設計にあたって最も配慮したものは,-60℃に及ぶ低温下,低地から4,000mに至る高地で使用可能なこと,走行距離約6,000km,旅行期間5ヵ月の連続使用に耐えうること等の苛酷な条件についての対策である.このため,機関過給機,車両使用材料等の選定,カタピラおよび懸架バネ等の耐久性,車体等の保温,暖房その他については,事情の許すかぎり試験研究を行ない,これらの資料および前回の観測時の実績等を基礎として,基本設計を行なった.なお,本雪上車は1965年1月末試作を終え,北海道において試験を行なう予定である. This snow car is designed for the travel through the Antarctic inland. The main requirements for the design are as follows : 1. Performance of the engine at high altitudes must be improved so that the car can climb up to 4,000 m. 2. Durability of components and parts at extremely low temperatures (about-60℃) must be ensured. 3. The tractive force of the car must be strong enough to two sleds which weigh more than 6 tons. 4. The cabin must be of the cabover type and perfectly protected from blizzards. Since the car must be designed and constructed within a year, we decided to improve the Type 61 Snow Car currently in use by the Japan Ground Self Defence Force, so as to satisfy the above requirements. Before designing, we have studied and tested the performances of engine and turbochargers, selection of materials, durability of track plates and suspension springs and other parts. The car has about 8.5 tons gross weight, 0.20 kg/cm^2 ground contact pressure and accommodates a crew of 3 men. The body is of a cabover type, and the cabin is equipped with heating apparatus, ventilators, beds, cooking apparatus and others. The observation instruments and communication equipments also can be installed in it. The car has a 140 PS diesel engine and can cruise at a speed of about 5 km/h when towing 3 sleds weighing totally about 8 tons. The construction of the car will be completed at the end of January 1965, and then, the car will be tested in Hokkaido. Errata | http://id.nii.ac.jp/1291/00007371/ departmental ...